Deconstruction of compulsory bipedal in dance (Revista Educação, Artes e Inclusão, 2020)
The presence of any kind can trigger a series events to the body. The body as corpomedia, that is, media of its state, of each moment of its state, the poetic discourses that emerge there are understood as historically produced and corresponds to the experiences that constitute the body. Considering this, the investigation of the construction of the dance in multiple bodies, the propriety of the body as a living, cognitive and self-organizing process becomes evident. However, when it comes to the disable body dances, the kickback about that body. The sovereignty of bipedal thinking that excludes these people as unfit and unproductive, regardless of any advance in the field of dance, is evident.  The dance in this context, is a clipping (micro space) that reveals, in itself, all social behavior (macro space). We understand that this field of knowledge construction that is dance will collaborate in intersectionality whit other areas, based on how it establishes and understands body relations.  Considering Dance and body that dances as a clipping o four social structure, it is possible to perceive discourses of hegemonic thinking that maintain exclusive functional and body patterns in relation to people with disabilities.